Evaluation of electrical properties, oxidation and corrosion behavior of Fe and Bi added Sn-0.7 Cu lead-free solder alloy / Syed Hassan Abbas Jaffery - Syed Hassan , Abbas Jaffery (2017)
Before the legislations against the usage of lead, Sn-Pb solders were considered as the most efficient choice as a solder interconnect material in electronic and electrical industries. However, the toxicity of lead has raised serious ecological and human health concerns. Sn-Ag-Cu series is considered as the most promising replacement for Sn-Pb alloys. However, the composition has been restricted due to the fragile behavior of solder joints and high cost. This study aims on effect of Fe and Bi addition on the electrical properties, oxidation and corrosion behavior of Sn-0.7Cu solder alloy. The properties of Sn-0.7Cu solder alloy is compared with Sn-0.7Cu-0.05Fe, Sn-0.7Cu-0.05Fe-1Bi and Sn-0.7Cu-0.05Fe-2Bi solder alloys. Addition of Fe and Bi in Sn-0.7Cu alloy causes significant changes in the microstructure and chemical state of Tin. The minor alloying addition of Fe to binary Sn-0.7Cu alloys result in the formation of high resistive FeSn2 intermetallic compound. Addition of Bi forms a substitutional solid solution with Sn in the primary ß-Sn dendrites of the solder alloy. The changes in microstructure and chemical states are correlated to the electrical resistivity of alloys. The electrical resistivity of alloys increases with the alloying of Fe and Bi. Thermal aging results in the refinement of microstructure. The refinement in microstructure results in improved electrical properties. The weight gain graphs indicates that the addition of Fe and Bi results in slight degradation of oxidation resistance of Sn-0.7Cu solder alloy. Addition of Fe does not have significant impact on the chemistry of oxide layer. However, the addition of Bi leads to the formation of Bi2O3 along with SnO and SnO2. The alloys were also subjected to potentiodynamic polarization in 3.5 wt.% NaCl solution. The addition of Fe and Bi degrades the corrosion resistance of alloys. Surface morphology results reveals a much smoother morphology of Sn-0.7Cu alloy. Smooth corrosion products promotes in the formation of passive layer, hence providing higher resistance to corrosion. Electrochemical impedance spectroscopy (EIS) results reveals high resistance and low capacitance values of Sn-0.7Cu solder alloy, representing the formation of compact and adherent passive film on the surface of alloys. The electrical properties, oxidation and corrosion behavior of modified solder alloys are better than Sn-Pb and commercially used SAC solder alloys.